Mechanisms of chemotherapy-induced behavioral toxicities - Vichaya, Elisabeth G.; Chiu, Gabriel S.; Krukowski, Karen; Lacourt, Tamara E.; Kavelaars, Annemieke; Dantzer, Robert; Heijnen, Cobi J.; Walker, Adam K. (Frontiers in Neuroscience, 2015)
While chemotherapeutic agents have yielded relative success in the treatment of cancer, patients are often plagued with unwanted and even debilitating side-effects from the treatment which can lead to dose reduction or even cessation of treatment. Common side effects (symptoms) of chemotherapy include (i) cognitive deficiencies such as problems with attention, memory and executive functioning; (ii) fatigue and motivational deficit; and (iii) neuropathy. These symptoms often develop during treatment but can remain even after cessation of chemotherapy, severely impacting long-term quality of life. Little is known about the underlying mechanisms responsible for the development of these behavioral toxicities, however, neuroinflammation is widely considered to be one of the major mechanisms responsible for chemotherapy-induced symptoms. Here, we critically assess what is known in regards to the role of neuroinflammation in chemotherapy-induced symptoms. We also argue that, based on the available evidence neuroinflammation is unlikely the only mechanism involved in the pathogenesis of chemotherapy-induced behavioral toxicities. We evaluate two other putative candidate mechanisms. To this end we discuss the mediating role of damage-associated molecular patterns (DAMPs) activated in response to chemotherapy-induced cellular damage. We also review the literature with respect to possible alternative mechanisms such as a chemotherapy-induced change in the bioenergetic status of the tissue involving changes in mitochondrial function in relation to chemotherapy-induced behavioral toxicities. Understanding the mechanisms that underlie the emergence of fatigue, neuropathy, and cognitive difficulties is vital to better treatment and long-term survival of cancer patients.